Secondary Metabolite Composition and Bioactivity of Genus Albizia: A Review - Momodou Salieu Sowe; Anayo Christian Etonihu (JSMARTech: Journal of Smart Bioprospecting and Technology, 2023)
Traditional medicine is being revalued all around the world because of considerable research on various plant species and their therapeutic properties. Traditional medicinal beliefs and practices are deeply rooted in The Gambia, and forest resources are a source of plants for medicine. A study has estimated the presence of one hundred and fifty (150) plant species in The Gambia, distributed between 28 different plant families. Among the plant species, Albizia seems to possess numerous pharmacological properties. Albizia plants are high in secondary metabolites, according to phytochemical investigations, and pharmacological tests of plant extracts have demonstrated antibacterial, anti-inflammatory, and analgesic effects. Albizia plant components are used in traditional medicine to cure a variety of diseases like lung infections, asthma, pile, diarrhea, gonorrhea, ulcers, hemorrhoids, anxiety, depression, and insomnia. Different solvent extracts of the genus Albizia have demonstrated excellent efficacy against S. Typhimurium, S. Enteritidis, S. Dublin, S. aureus, E. coli, V. parahaemolyticus, B. cereus, S. aureus, and S. pyogenes. The radical scavenging activity of the genus Albizia exhibits a significant antioxidant activity with relatively high EC50 and IC50 values.